Ride-Hailing Platforms in Brazil: Regulatory Challenges in Times of Crisis - Jeronimo, Rodrigo Constantino [UNESP] (Taylor & Francis, 2024)
By addressing the growth of digital platforms in Brazil over the past decade, as well as the search for regulation aiming at improving digital workers’ conditions, this article discusses regulatory challenges in the face of these companies’ increasing economic and political power. With the adoption of the transactional approach of John R. Commons, we discuss the stages and consequences of the spread of digital platforms, highlighting the emergence of new conflicts in driver-platforms and driver-state transactions, thus calling for regulation; as well as the political obstacles of regulation, considering platforms economic power and worker’s expectation about their activities under regulation. We argue that these features challenge the regulatory efforts aimed at achieving reasonableness in digital labor transactions, by reducing public pressure towards “better” practices, such as improved working conditions, wages, and management.
Keywords: Brazil; regulation; ride-hailing platforms